Efeitos da operação de hidrelétricas isoladas e em cascata sobre o regime hidrológico subdiário em rios afluentes ao Pantanal - Figueiredo, Juliane Stella Martins Costa de (2020)
The operation of hydroelectric projects, based on the daily demand for electricity, causes variability in the subdaily hydrological regime of rivers and, consequently, changes in their ecological process. The expansion of the installation of small and cascading hydroelectric plants can produce cumulative effects and, thus, impact not only rivers, but a set of hydrographic basins and large areas. Thus, this study seeks to analyze the effects of isolated and cascading hydroelectric projects, in rivers affluent to the Pantanal, on a subdaily analysis scale, in order to (i) to identify the projects that most change the subdaily hydrological regime and the period of greatest change; (ii) identify which are the most altered subdaily hydrological indicators; (iii) quantify the magnitude of the hydrological change by hydroelectric project and (iv) evaluate the effect of the hydraulic and hydrological characteristics of isolated and cascade hydropower projects on the subdaily hydrological regime. The study area involves the Hydrographic Region of Paraguay, where the Pantanal is contained, and which has 56 hydroelectric plants in operation and about 100 with expected installation. For the analyzes, subdaily flow data were used, available on the Hydro Telemetry Portal of the National Water Agency, in order to apply them in Subdaily Hydrological Indicators and, later, evaluation of the magnitude of the hydrological effects, calculating Daily Hydrological Change Rates. The results showed that only 50% of the telemetric stations studied were able to be used for the calculation of the Subdaily Hydrological Indicators, so that they presented a frequency of failures below 20%. After that, the calculation of the Subdaily Hydrological Indicators and the Daily Hydrological Change Rates, with the respective statistical analyzes, show that, regardless of the size of the projects and the system adopted isolated or in cascade, the hydroelectric operations changed the regime subdaily hydrological in similar proportions, so that, on average, 74.4% of the IHS were altered, with an average magnitude of 205%. Such results are indications that the enterprises in operation and those that will be installed, if not properly managed, may affect the hydrological, hydraulic, ecological and social characteristics of the hydrographic basins involved. Thus, it seeks to highlight the need for a balance between the generation of hydroelectric energy and the conservation of water resources.